Development Of A Small Scale Corexy Type 3D Printer - Yeoh, Xing Yuan (2021)
The 3D printing technology is a high demand field of study as every components of the 3D printing technology required sufficient and detailed research and development before it can reach the functional stage today; expand, improve and grow in the future. It can be claimed that 3D printing is among the important field to study for the development and enhancement of skills to prepare ourselves for the future world of industry 4.0. This project aims to step up the normal printing speed of low-cost FDM 3D printer in the market priced below MYR 1, 000 which usually in the coreXZ structure by the structural change and other modifications made. This research provides a detailed development process of a small scale coreXY type 3D printer from scratch. The developed prototype targeted to achieved more than 80mm/s in normal printing speed with the manufacturing cost limited to MYR 1, 000. This project can expose us to various fields included but not limited to mechanical design, electronics circuit connection, components selection, firmware configuration, quality control, 3D printing knowledge, idea realization and material study. For the prototype developed, the base model of the design derived from Hypercube model by Tech2C. The firmware used is the open source Marlin Firmware 2.0.7. With the improvement on printing speed, a shorter printing time permissible for the same model and the efficiency of the printer increased. Besides, the operation cost mainly induced by the heating elements, hot end and heated bed can be reduced. In short, more parts can be printed in a shorter period of time, it takes shorter time for product realization and able to promote the creativity and innovation of people in a budgeted way. This project has achieved a 100mm/s normal printing speed for the FDM 3D printer developed using core XY structure that can be claimed to have escaped from the “slow” category among the 3D printers in the similar price range.